The Importance of Energy Management in Public University Campuses - Davide Di Battista; Emanuele Del Rosso; Anna Tozzi (Journal of Sustainability Perspectives, 2024)
Energy consumption has gained great attention in recent years, particularly due to the changes in the geopolitics situation and the difficulty in ensuring security in energy sources supply. Several national and international governments set new and more stringent targets to reduce fossil fuel consumption, also proposing specific short-term and mid-term actions. For instance, the Italian Government emanates the Italian National Plan to Reduce Natural Gas consumption in 2022, particularly focused on residential, commercial and public buildings. University of L’Aquila takes inspiration from this planning, to revise its energy management and promote technical actions and a communication campaign aimed at reducing energy consumption. The short-term actions are related to the HVAC plants management of its building: a) shortening the heating days and reducing the daily hours HVAC switching on; b) slight reduction of the indoor comfort temperature; c) reduction of lighting time and intensity. Moreover, virtuous behavior has been encouraged with a communication campaign addressed to employees and students. Results obtained in only one year are very exciting: the natural gas consumption has been reduced more than 20% in academic year 2022/2023, with respect to average values of previous years, with an estimated GHG emissions avoided close to 140 tCO2 for the specific faculty considered. These results are very positive in the GreenMetric perspective, and they boost the importance also of a quite simple but effective energy management strategy and diffusion of awareness on energy and environmental issues.